2006
DOI: 10.1080/08916930600622819
|View full text |Cite
|
Sign up to set email alerts
|

National registry of patients with juvenile idiopathic inflammatory myopathies in Hungary—Clinical characteristics and disease course of 44 patients with juvenile dermatomyositis

Abstract: Idiopathic inflammatory myopathies (IIMs) are systemic autoimmune diseases characterized by chronic muscle inflammation resulting in progressive weakness and frequent involvement of internal organs, mainly the pulmonary, gastrointestinal and cardiac systems which considerably contribute to the morbidity and mortality of the IIMs. Aim of this study was to present clinical characteristics, disease course, frequency of relapses and survival in patients with juvenile dermatomyositis (DM). A national registry of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
24
1
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 72 publications
10
24
1
6
Order By: Relevance
“…Serious or fatal pulmonary complications in JDM have been described in case reports 4 5. Also, pulmonary involvement in JDM has been described in studies not primarily addressing this aspect; asymptomatic significant restrictive impairment being found in 14/17 patients6 and ILD in 7% to 19% 79…”
Section: Introductionmentioning
confidence: 99%
“…Serious or fatal pulmonary complications in JDM have been described in case reports 4 5. Also, pulmonary involvement in JDM has been described in studies not primarily addressing this aspect; asymptomatic significant restrictive impairment being found in 14/17 patients6 and ILD in 7% to 19% 79…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22] Previously, the most commonly described ILD found in dermatomyositis/polymyositis was usual interstitial pneumonia. 23 However, as in systemic sclerosis, recent reviews now have found that the most commonly described pathologic fi nding is nonspecifi c interstitial pneumonia.…”
Section: Dermatomyositis/polymyositismentioning
confidence: 99%
“…One-year survival has varied from 83% to 95%, whereas 5-year survival has ranged from 63% to 95%, with 9-year or greater survival rates ranging from 53% to 100%, depending on the disease subtype. 24,26,34,35,43,151,152 All of these survivals are better than the 50% mortality for DM that Bohan and Peter 4 cited as the natural disease course before corticosteroid therapy.…”
Section: Prognosismentioning
confidence: 93%
“…Today, these are much lower, as newer studies found mortality at 1.5% 39 and even 0%. 34 DM has a bimodal age distribution, with patients with JDM not having a cancer association, and adults having associated malignancy at variable rates. One series of 120 patients with JDM found no cancers.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation